Effectiveness of 20 hour lactation management course (LMC) in improving the breastfeeding knowledge of professional nurses in tertiary hospital in Gauteng - Makhudu, Nomonde (My University, 2017)
Background: In-service training, such as the Lactation Management Course (LMC), is a form of ongoing professional development for staff members; however, there is no formal way of measuring or of assessing its effectiveness. It is not known if the training improves the service delivery of practices that promote breastfeeding and improvement of the quality of care which will, in turn, improve the breastfeeding rates in the institution (PubMed, 2010). Aim: This study evaluated the effectiveness of the 20-hour LMC training to improve breastfeeding knowledge of professional nurses and midwives working in mother and child units in an academic institution in the Johannesburg region. Methodology: An experimental, pre-test/post-test control group design that involved 47 participants was used to conduct the study (Brink, 2012). The Statistical Package for Social Sciences (SPSS) was used for data analysis. A descriptive statistical analysis, using a paired t- test analysing the means and standard deviations, was conducted and the data from the pre- and post-test results were compared. Results: The study showed that, overall, the professional nurses and midwives’ level of knowledge of breastfeeding improved after the training, indicating that the LMC training is an effective way to improve breastfeeding knowledge. This was evident as there was an increase of correct answers post-training in comparison to the pre- training results, even though it was smaller than expected. Recommendation: The recommendation is that LMC training is offered to all professional nurses and midwives working in a mother and child department, and that, where possible, advanced training should be provided to professional nurses and midwives who already possess in-depth knowledge about breastfeeding. The LMC may need to be reassessed as it not yielding results that bring about the necessary change in practice in the hospital under study.
Research Report submitted in partial fulfillment of the requirements for the Master of science in nursing education 2017
Keywords: Lactation Management Course (LMC); Breast Feeding; Infant Mortality